Qualitative research approach for the conceptual understanding of spirituality for healthcare service users: a methodological guide - Mohamad Shariff, Nurasikin (IIUM Press, 2020)
This is a methodological paper which addresses the need to conceptualize the characteristics of spirituality from the perspective of healthcare service users by using ualitative approach. The need to provide a conception of spirituality as derived from empirical data lead to the justification of choice for the constructivist grounded theory over other qualitative methodologies. This paper highlights the subjective nature of spirituality that suits with the symbolic interactionist and interpretivist as philosophical paradigm underpin such approach in qualitative inquiry. The implication of applying qualitative approach and constructivist grounded theory is that the empirical work may portray the contextual nature of spirituality for the population of interest, especially when it is arguable non-applicable to global context.